High on-treatment platelet reactivity – definition and measurement - Cattaneo, Marco (Thrombosis and Haemostasis, 2013)
In the last decade, several studies revealed inter-patient response variability to antiplatelet agents: patients who display negligible or no responses to these drugs are considered poor responders, or “resistant” to treatment. In order to identify poor responders to an antiplatelet drug, laboratory tests of platelet function that specifically explore the platelet activation pathway that is targeted by the drug should be utilised. In addition, they should be performed both at baseline and during treatment: however, most studies explored platelet function during antiplatelet treatment, in order to identify those patients with “high on-treatment platelet reactivity” (HPR), which exposes them to increased risk of major adverse cardiovascular events (MACE). Many tests of platelet function have been used, most of which are able to identify patients at risk of MACE. Unfortunately, universal cut-off values for HPR have not been clearly established yet. In addition, the concordance among different tests in the identification of patients at risk is very poor and the most effective and safe treatment for patients at risk is still unknown.
Keywords: Antiplatelet agents; platelet pharmacology; arterial thrombosis; clopidogrel; aspirin